Biosorption of heavy metal and dyes : a promising technology leather wastewater treatment - Rosales, E. (2011)
The presence of dyes and heavy metals is usual in industrial processes like chrome tanning in tannery industry and their removal may be an environmental problem. Different techniques were developed and applied for the treatment of dyes and heavy metals in effluents. Among them, adsorption showed to be an economic, simple operation and an effective technique. Zeolites have a strong affinity for cations of transition metals, but only little affinity for anions and non-polar organic molecules. The application of a zeolite to heavy metal removal may be improved by the presence of microorganisms. The aim of this work is the treatment of an effluent containing dyes and toxic metals. Several operation parameters such as pH, concentration and kinetic behavior were studied. This innovative process for treating dyes and heavy metal effluents showed that the zeolite-biomass system is able to perform the removal of a combination of Azure B and chromium(VI). A mixture of dye and metal solutions was treated reaching a removal higher than 50% in the case of chromium (VI) and higher than 99% for dye, in 8 days.